2009
DOI: 10.1136/jcp.2009.065102
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor β expression in pleomorphic adenomas of the parotid gland

Abstract: This is thought to be the first study of ERbeta in pleomorphic adenomas of the salivary gland. Findings support ERbeta as the major ER in salivary glands, and provide evidence that ERbeta may have a role in the development of pleomorphic adenomas of the salivary gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(47 reference statements)
1
12
1
Order By: Relevance
“…Overexpression of ER-β was described in four cases of pediatric MEC and in ACC cell line [ 32 ], while nuclear overexpression of ER-β was detected also in 71% of ACC FPPE tissues, with the average expressions higher in women, and in the cases with a cribriform architecture [ 11 ]. ERβ was also detected in several cases of PA of the salivary gland [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of ER-β was described in four cases of pediatric MEC and in ACC cell line [ 32 ], while nuclear overexpression of ER-β was detected also in 71% of ACC FPPE tissues, with the average expressions higher in women, and in the cases with a cribriform architecture [ 11 ]. ERβ was also detected in several cases of PA of the salivary gland [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the expression and role of AR in SGTs are well documented [ 9 , 10 ]. The other estrogen receptor (ERβ) was described in salivary gland adenocarcinoma cell lines and certain salivary gland carcinomas such as AdCC and Pleomorphic adenoma (PA) [ 11 , 12 ]. The structure of ERβ is homologous to that of ERα and its DNA-binding domain is 96% conserved compared to ERα, suggesting that ERβ could bind the same target genes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from the analysis of the archival data, the frequency of pleomorphic adenomas decreased in comparison with the statistics of the majority of foreign sources (according to EM Osipian, 2011; YH Matiakin 2010), the frequen cy of pleomorphic adenomas was 6190%) [13]. In turn, the domination of women in this neoplasm indicates a possible endocrine dependence of the tumour, namely the presence of oestrogen beta receptors in tumour tis sues [19]. Unlike women, for men the tumours of the sali vary glands were dominated by adenolymphomas (Warthin tumour), at 72.27%, which coincides with the data of most literary sources, in which the gender ratio (male : female) is between 3 : 1 and 5 : 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although oestrogen receptor α may be expressed in low levels in normal salivary tissue, it appears that oestrogen receptor β is the main oestrogen receptor in normal salivary tissue. A series of 49 pleomorphic adenomas showed that oestrogen receptor β was expressed in almost twice as many normal salivary tissues and pleomorphic adenomas as oestrogen receptor α [ 134 ]. Progesterone receptors do not appear to present in PAs [ 93 ].…”
Section: Genetics and Prognosismentioning
confidence: 96%